PERAN GURU PENDIDIKAN AGAMA KATOLIK DALAM MENINGKATKAN PENGENDALIAN DIRI REMAJA DI SMA NEGERI TAEKAS - Mones, Anselmus Yata; Un, Damianus (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2021)
The purpose of this study was to determine the role of Catholic religious teachers at Taekas State High School in relation to adolescent self-control and to measure the effectiveness of these efforts in increasing the self-control of Taekas Senior High School students. Teachers are people who have knowledge, and experience, and are fully responsible for the educational process of their students by example and personality so that they can direct students to achieve educational goals. Catholic religious education is faith education that is carried out in a planned manner, strengthens students' faith in God Almighty in accordance with Catholic religious teachings, and prepares students to become useful human beings for the State and the Church. Adolescent self-control is a process of growth between childhood and adulthood, which is between the ages of 13-17 years in which a person seeks his identity and refuses to act contrary to human norms or to restrain behavior that is painful or detrimental to others. The method used in this study is a qualitative approach, where the researcher uses direct interviews with respondents as a tool to collect data. The results of the study found several efforts made by the teacher and the results obtained in improving adolescent self-control at Taekas State High School. Efforts include: first, increasing student attendance at school. Second, is the increased activeness of students in the classroom. Third, most of the students are orderly by school rules and regulations. Fourth, increasing student achievement results. Fifth, student behavior is in accordance with what is expected so that unwanted things do not happen.